Foundations of Pension Legislation in Russia, France, and Great Britain: An Investigation on Political Doctrines in the 17-20th Centuries - Aleksandrova, Anna Victorovna (Journal of History Culture and Art Research, 2021)
The article considers the process of forming conceptual foundations of pension legislation in Russia, France, and Great Britain. The scientists of 17-18th centuries substantiated the right to life and human dignity as the most important human rights. Later, in 19-20th centuries, the right to a dignified existence, the right to assistance from the state in case of disability were formulated. The need for the livelihood of the elderly was recognized by most authors, however, there were serious discrepancies regarding the methods for provision and sources of financing payments. The article considers the pension laws adopted in Great Britain, France, and Russia in the first half of the 20th century that reflected the above concepts anyway. The French pension legislation has embodied the insurance model of pension security and was strongly influenced by Bismarck legislation, while the British one reflected the legislator’s desire to abandon the extremes of the ideology of individualism and ‘self-help’ through the introduction of state budget pensions. In Russia, the origin of compulsory social insurance took place almost simultaneously with Western European countries; however, this process was broken by the revolutionary events of 1917. As a result, a state budgetary pension system was created in Soviet Russia. The author comes to the conclusion about the mutual influence of various models of pension protection, legalized in the first half of the 20th century in the countries under consideration, as well as the special role of social solidarity concepts and the generational contract for the formation of these models.